Journey to the common good - Brueggemann, Walter (Louisville, KY : Westminster John Knox Press, 2010)
Brueggemann brings together contemporary cultural analysis with challenging biblical insights and offers a hopeful road map for our shared human journey.
The journey to the common good : faith, anxiety, and the practice of neighborliness -- The continuing subversion of alternative possibility : from Sinai to current covenanting -- From vision to imperative : the work of reconstruction.
Includes bibliographical references and index.
Keywords: Bible. -- Criticism, interpretation, etc; Common good -- Biblical teaching